The impact of cytoreductive nephrectomy on survival outcomes in patients with metastatic renal cell carcinoma receiving immunotherapy: An evidence-based analysis of comparative outcomes - Li, Kun-peng; Chen, Si-yu; Wang, Chen-yang; Li, Xiao-ran; Yang, Li (Frontiers in Immunology, 2023)
Abstract Purpose: The prognostic impact of cytoreductive nephrectomy (CN) for metastatic renal cell carcinoma (mRCC) in the era of immunotherapy is yet to be determined. The aim of our study is to evaluate the correlation between CN and outcomes in the setting of mRCC treated with immunotherapy. Methods: We conducted a systematic search of the Science, PubMed, Web of Science, and Cochrane Library databases to identify relevant studies published in English up to December 2022. The results were presented as hazard ratio (HR) with 95% confidence intervals (CIs) for overall survival (OS) was extracted to assess their relevance. The study was registered with PROSPERO (CRD42022383026). Results: A total of 2397 patients were included in eight studies. The CN group was observed to be correlated with superior OS compared to the No CN group (HR = 0.53, 95% CI 0.39–0.71, p < 0.0001). Subgroup analysis according to the type of immunotherapy, sample size, and treatment line of immune checkpoint inhibitor revealed that CN group had a superior OS in all subgroups. Conclusions: CN is associated with a better outcome in terms of OS benefit in selected patients with mRCC treated by immunotherapy, but further studies are required to verify the conclusions.